Análise da ocupação veicular para a inserção de beneficiários no transporte coletivo urbano - Sérgio Silvestrini Ferreira (2013)
In the majority of Brazilian cities it is easily identified the following antagonistic situation in buses of the public transport system: crowded vehicles and repressed demand on peak hours, and empty buses on off peak hours, beating the seats as buses transit users say. There can be many causes: the lack of planning, investing, financing, supervision, control, monitoring of the operation. What are the thoughts of the financial disabled, those in difficulties to afford the fares, when they see buses running empty during certain periods of the day? Well, if buses operate with an idle capacity, wouldnt it be humanly correct to promote social inclusion for people in need, for example, unemployed people, even if temporarily, at those periods? By means of an applied research, this study aims at presenting the development of a method that, in theory, is capable of monitoring and evaluating critical occupancy rates in urban public transportation considering the route segments with the highest ridership demand. The main objective is to detect the periods of the day when occupancy rates are lower than the maximum permitted by contract between local authority and public transportation concessionaires, which results in the possibility of inclusion of beneficiaries of the transit system without the need of paying full fares. The methodology was applied in a case study in Belo Horizonte city based on the treatment and statistical analysis of databases generated by the Automatic Fare Collection system AFC. The data processing allowed the determination of the Passenger Occupation Index for the critical road segment for weekdays of October 2012 considering each one of the 653.000 trips. The results allowed the formulation of a new indicator of comfort level, named Desirable Comfort Index, necessary to define the fleet idle capacity during operation and to quantify the number of beneficiaries that could use the public transport with fare discounts during specific periods of the day. AFC applications are responsible for controlling and managing the proposed method. As a social contribution, this study demonstrates that investments in bus technology could make buses accessible to excluded categories until now, as well as cheaper, attractive and reliable, without affecting either the level of quality or the financial balance of the system.